Effects of alkaline and ultrasonication on duckweed (Wolffia arrhiza) protein extracts’ physicochemical and techno-functional properties - Nitiwuttithorn, Chotika; Wongsasulak, Saowakon; Vongsawasdi, Punchira; Yongsawatdigul, Jirawat (Frontiers in Sustainable Food Systems, 2024)
Wolffia is a protein-rich aquatic plant with the potential to help address food sustainability issues; however, a more efficient extraction process must be sought due to limited yield with conventional methods. This study aimed to investigate the effects of duckweed forms (fresh and dried), duckweed-to-aqueous solution ratio (DSR), as well as alkaline and ultrasonication extractions on yields, physicochemical and techno-functional properties of duckweed protein extracts (DPE). Three extraction methods were used: alkaline extraction (AE), ultrasoundassisted alkaline extraction (UAAE), and ultrasound-assisted water extraction (UAWE). The study showed fresh duckweed resulted in a 2.5-fold higher yield and protein recovery than oven-dried duckweed. UAE significantly enhanced extraction yield and protein recovery. The optimal extraction process was a DSR of 1:6 using UAAE at pH 8.5, resulting in a 16% yield and 34% protein recovery. Furthermore, the study found that UAE facilitated the extraction of non-polar/hydrophobic amino acids while AE proved to be efficient in extracting sulfurcontaining amino acids. This study, for the first time, revealed the role of UAE and AE in promoting the extraction of different profiles of amino acids. The DPE produced using UAAE contained 65% protein, meeting the WHO/FAO/UNU recommended protein intake for preschool-aged children. Furthermore, the DPE exhibited excellent emulsifying properties and oil-holding capacity comparable to commercial soy protein isolates. Overall, UAAE was identified as a promising approach for producing techno-functional and nutritious protein ingredients from Wolffia. The resulting DPE proved to show great potential for functional plant-based food and feed applications.